1999
DOI: 10.1111/j.1572-0241.1999.01082.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gastric Mucosal Lesions in Patients With Celiac Disease: A Prospective Controlled Study

Abstract: According to our results, celiac disease patients presented a similar prevalence of gastric mucosal abnormalities compared with the control population. Evidence of H. pylori infection was very high compared with the prevalence in the general Argentine population. As a particular observation in our celiac population, the disease was rarely associated with lymphocytic gastritis. We suggest that the chronic inflammatory state evidenced by a gastric mucosal lymphocyte infiltration may be secondary to the combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 26 publications
1
25
1
4
Order By: Relevance
“…The prevalence of Hp infection among 28 CD patients and in patients without CD was 82% and 86.2% respectively. The difference is not statistically significant, according to previous studies by Diamanti et al and Luzza et al that showed a difference in terms of prevalence not statistically significant [27,28,29]. In addition there was no relation between gastritis and severity of mucosal damage in CD.…”
Section: Resultsmentioning
confidence: 42%
“…The prevalence of Hp infection among 28 CD patients and in patients without CD was 82% and 86.2% respectively. The difference is not statistically significant, according to previous studies by Diamanti et al and Luzza et al that showed a difference in terms of prevalence not statistically significant [27,28,29]. In addition there was no relation between gastritis and severity of mucosal damage in CD.…”
Section: Resultsmentioning
confidence: 42%
“…Despite high specificity of autoantibodies, this finding would provoke the discussion on seronegative cases and question the sensitivity of serological tests. Although, microenteropathy could be a result of any other intestinal disorder, from previous experience we learned those negative serological tests were less reliable in symptomatic cases presenting with a milder enteropathy (28)(29)(30). Based on this evidence if we believe that specificity of serology (tTGA) is beyond 98% and if we also believe that seronegative cases presenting with milder enteropathy exist, we might be able to recognize that an even higher proportion (>8%) of our CD patients might present with dyspepsia.…”
Section: Discussionmentioning
confidence: 99%
“…We know that damages in gluten sensitivity are not confined to the small intestine (17) and no every gluten sensitive patients develop severe mucosal small bowel abnormality. Several studies have demonstrated that continues exposure to gluten may damage the structure and function of the gastric mucosa in gluten-sensitive patients (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Наличие межэпителиальных лимфоцитов без атрофии ворсинок служит поводом для проведения дифферен-циальной диагностики, в том числе с геликобактерной инфекци-ей. Большинство исследователей отметили снижение частоты Н. pylori среди пациентов с целиакией по сравнению с контролем [19][20][21][22][23], в некоторых исследованиях не выявлено различий [24][25][26], а в одной работе обнаружено повышение частоты развития инфекции Н. pylori у больных целиакией [27]. Некоторые авторы связывают инфекцию Н. pylori с риском развития аллергических, атопических и других воспалительных заболеваний [28][29][30].…”
Section: терапевтический архив 2 2016unclassified